Navigating Critical Theory and Postmodernism: Social Justice and Therapist Power in Family Therapy. Issue 3 (21st July 2016) - D'Arrigo‐Patrick, Justine; Hoff, Chris; Knudson‐Martin, Carmen; Tuttle, Amy
Abstract : The family therapy field encourages commitment to diversity and social justice, but offers varying ideas about how to attentively consider these issues. Critical informed models advocate activism, whereas postmodern informed models encourage multiple perspectives. It is often not clear how activism and an emphasis on multiple perspectives connect, engendering the sense that critical and postmodern practices may be disparate. To understand how therapists negotiate these perspectives in practice, this qualitative grounded theory analysis drew on interviews with 11 therapists, each known for their work from both critical and postmodern perspectives. We found that these therapists generally engage in a set of shared constructionist practices while also demonstrating two distinct forms of activism: activism through countering and activism through collaborating. Ultimately, decisions made about how to navigate critical and postmodern influences were connected to how therapists viewed ethics and the ways they were comfortable using their therapeutic power. The findings illustrate practice strategies through which therapists apply each approach. Abstract : Video Abstract